TOPOGRAPHIC-ANATOMICAL FEATURES OF FORMATION OF INTRAHEPATIC BILE DUCTS - Алієва, Н.Г. (World of Medicine and Biology, 2025)
Topographic and anatomical features of intrahepatic bile ducts are an important aspect of surgery and gastroenterology. Therefore, we have studied options for the formation of the right, left and common hepatic ducts using the method of macroscopic preparation. It was determined that the common hepatic duct was formed from three ducts in 4 of 28 preparations, and from four ducts in 15. The right hepatic duct is formed by the segmental ducts of the right inferior, superior, and caudate lobes, and the left hepatic duct is formed by the segmental ducts of the left anterior, posterior, and quadrate lobes. In 28 preparations, 5 had no right hepatic duct, 3 had no right upper segmental duct, 1 had the right hepatic duct receiving branches from the left hepatic and accessory ducts, 3 had the ducts of the caudate lobe opening directly into the common hepatic duct, and 2 had accessory hepatic ducts.